My life on mountain railroads - Gould, William John Gilbert, 1888-1961 (Utah State University Press, 1995)
In 1917, Gilbert Gould achieved his dream to be an engineer, and began running engines for the Denver & Rio Grande and later for the Utah Railway. He was a natural storyteller, and his recollections are entertaining and historically rewarding.